The Value Relevance of Sustainability Disclosure Quality - Aulia Fuad Rahman; Desi Tri Kurniawati; Ayu Aryista Dewi; Kholilah Kholilah (Jurnal Ilmiah Akuntansi, 2023)
In the contemporary landscape, ESG (environmental, social, and governance) performance has emerged as a pivotal concern for capital market investors. Despite its prominence, the ongoing debate in the literature regarding the value relevance of ESG underscores the need for empirical insights. This study addresses this gap by investigating the moderating role of ESG disclosure quality in shaping the relationship between earnings, annual changes in earnings, and stock returns. Drawing on a dataset comprising 254 firm-year ESG reports in Indonesia from 2017 to 2022 and employing panel data regression, the research unveils compelling results. It demonstrates that high-quality ESG disclosure not only reinforces the impact of earnings and annual changes in earnings on stock returns but also signifies a lower risk of future sustainability and long-term growth. These findings substantiate the idea that robust integration of sustainability principles in business practices contributes significantly to the creation of shareholder value. Importantly, this research carries profound implications for Indonesian companies, emphasizing the critical role of ESG disclosure in fostering sustainable business practices and enhancing shareholder value in the evolving landscape of capital markets.